THEORETICAL ANALYSIS OF THE DEPENDENCE OF TRACTION PROPERTIES ON THE MACHINE DRIVE CHARACTERISTICS - Mishutin Evgeniy Yurevich; Ochilov Tura Yokubovich (Journals Park Publishing, 2023)
The article presents the results of a theoretical analysis jn the influence of the wheel formula and the connection diagram of the propulsions on the traction and coupling properties of machines.
Keywords: wheel formula, engineering machine, cross-axle differential, technological operations, traction properties.